2010
DOI: 10.1007/s00041-010-9158-x
|View full text |Cite
|
Sign up to set email alerts
|

Families of Spectral Sets for Bernoulli Convolutions

Abstract: We study the harmonic analysis of Bernoulli measures μ λ , a one-parameter family of compactly supported Borel probability measures on the real line. The parameter λ is a fixed number in the open interval (0, 1). The measures μ λ may be understood in any one of the following three equivalent ways: as infinite convolution measures of a two-point probability distribution; as the distribution of a random power series; or as an iterated function system (IFS) equilibrium measure determined by the two transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…We first give some remarks on these questions, and answer a question of Dutkay and Jorgensen [3] in Section 2. We then consider the spectra of Bernoulli convolutions in Section 3, and obtain a sharp result which extends the corresponding result of Jorgensen, Kornelson and Shuman [13]. In the final section, we provide a structural property for the integer spectrum of a spectral self-affine measure μ M,D .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…We first give some remarks on these questions, and answer a question of Dutkay and Jorgensen [3] in Section 2. We then consider the spectra of Bernoulli convolutions in Section 3, and obtain a sharp result which extends the corresponding result of Jorgensen, Kornelson and Shuman [13]. In the final section, we provide a structural property for the integer spectrum of a spectral self-affine measure μ M,D .…”
Section: Introductionmentioning
confidence: 87%
“…The other results concerning the spectral property of the Bernoulli convolutions have been obtained in [12,9,7,6,13]. Usually the following two types of questions have often been considered: For what values of λ, is μ λ a spectral measure?…”
Section: Spectra Of Bernoulli Convolutionsmentioning
confidence: 98%
See 1 more Smart Citation
“…For the spectrality of μ1/false(2kfalse), Jorgensen and Pedersen first proved that for each kboldN+, the set Λ2k given by normalΛ2k=j=0finiteajfalse(2kfalse)j:aj{0,1}is a spectrum of μ1/false(2kfalse). Later, Jorgensen, kornelson and Shuman proved that if p2N+1 such that p<2(2k1)π, then pk2normalΛ2k is a spectrum of μ1/false(2kfalse). In 2011, Li showed that if p2N+1 such that p<2k1, then pk2normalΛ2k is a spectrum of μ1/false(2kfalse).…”
Section: Introductionmentioning
confidence: 99%
“…} is a spectrum of 1∕ (2 ) . Later, Jorgensen, kornelson and Shuman [14] proved that if ∈ 2 + 1 such that < 2(2 −1) , then 2 Λ 2 is a spectrum of 1∕ (2 ) . In 2011, Li [19] showed that if ∈ 2 + 1 such that < 2 − 1, then 2 Λ 2 is a spectrum of 1∕ (2 ) .…”
Section: Introductionmentioning
confidence: 99%